If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40 = 3u Solving 40 = 3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3u' to each side of the equation. 40 + -3u = 3u + -3u Combine like terms: 3u + -3u = 0 40 + -3u = 0 Add '-40' to each side of the equation. 40 + -40 + -3u = 0 + -40 Combine like terms: 40 + -40 = 0 0 + -3u = 0 + -40 -3u = 0 + -40 Combine like terms: 0 + -40 = -40 -3u = -40 Divide each side by '-3'. u = 13.33333333 Simplifying u = 13.33333333
| 2.4(m-3.8)=-8.2 | | x+40+44=180 | | 65x+45=2505 | | 5x=3(x-2)+8 | | 5x+8=4x+24 | | 3(x-2b)=2(x-a)-5 | | -3x+10=-30+x | | 40x-10=y | | 2k+3k=15 | | 7x-81=31+3x | | 5x^2=-30 | | y/7=-9 | | 6-2(x+3)=8 | | q-5=16 | | 2x-10=6x+30 | | 7+x+7x= | | 14m-3x= | | 25x+4y=108 | | 117=7x-2 | | 4a+2b=360 | | 6x-18=4x-3 | | 3x+12=2x+x^2 | | 5(t+7)=2(2r+7) | | 5(u+5)-2= | | -x+5=6x-2 | | -5.5x+0.57=-1.64 | | .05(x+1)-1.5=9.3 | | 2x-4+2= | | (x+3)(8)=(7)(4) | | 25x+4y=25 | | -2-5x=2x-9 | | (y+6)-2y=14 |